Operation of large-volume cubic press above 8 GPa and 2500°C with a centimeter-sized cell volume using an optimized hybrid assembly. Issue 2 (3rd April 2021) - Song, Guozhu; Ma, Dejiang; Zhou, Xuefeng; Wang, Lingfei; Wei, Zheng; Xu, Chao; Wang, Wendan; Wang, Liping; Zhao, Yusheng; Wang, Shanmin
ABSTRACT: Large-volume cubic presses are widely used in scientific research and industrial applications. However, their pressure capability is often limited to 6 GPa, which severely restricts their applications under extended pressures. In this work, we report a newly designed hybrid cell assembly for cubic presses by embedding six WC pressure-enhancing blocks into the pyrophyllite pressure-transmitting medium, leading to profoundly increased pressure efficiency ( i.e. more than 40%), hence largely extended pressure conditions up to 8–9 GPa without sacrificing sample volume. Because of the optimized design, the expensive first-stage WC anvils are effectively protected, which makes the press routinely operated up to 8–9 GPa in avoiding damage of anvils. Through optimization of heating efficiency, temperature of the new assembly can reach above 2500°C. Using this high pressure cell, we have synthesized centimetre-sized polycrystalline cubic BN bulk sample by the direct transformation of hexagonal BN at 7.7 GPa and 2000°C. Successful implementation of large-volume cubic press up to 8–9 GPa and 2500°C would provide many opportunities for the synthesis of new materials on massive scale ( e.g. novel superhard compounds) and for the study of materials at extended pressures.